Effects of School-Based Educational Program on Backpack Carrying Behavior in Teenage Students. (March 2022) - NeJhaddadgar, Nazila; Tavafian, Sedigheh Sadat; Ziapour, Arash; Mehedi, Nafiul; Jamshidi, Ahmad Rreza; Gahvareh, Rohallah
One of the most serious issues is the growing prevalence of backaches among adolescent students as a result of carrying backpacks. The purpose of this study was to examine the impact of an education program (remedial information) on the school backpack carrying habits of adolescent students. The study sample consisted of 138 adolescent students aged 12 to 16 from 4 schools who were randomly assigned to either the experimental (N = 69) or control (N = 69) groups. The experimental group was subjected to a 6-week education program consisting of 6 sessions, whereas the control group received no educational intervention. During the pre-test and 3 months after the intervention, participants completed a questionnaire. The results (healthy items) were as follows: (1) carry as little as possible, (2) carry a school backpack on both shoulders, and (3) use lockers or something similar. After a 3-month follow-up, healthy items in the experimental group improved, but no significant changes were observed in the control group. When compared to the baseline, the experimental group's healthy backpack usage habits improved significantly at the post-test ( P  = .001). The current study's findings show that school-based education interventions on backpack behaviors improve the school-bag carrying habits of adolescent students.